The Effect of Investment Decisions and Funding Decisions on Company Value with Dividend Policy as Intervening Variables - Fakhrul Amal; Gregorius N. Masdjodjo (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
In a company has a long-term goal of optimizing the value of the company. The value of a company is a reflection of the value of its share price. In the process of maximizing company value, the company's management can implement three policies, namely financing/funding, investment, and dividend policies. The purpose of this study is to find out how the influence of investment decisions, funding decisions, and dividend policies on firm value in banks listed on the Indonesia Stock Exchange for the 2015-2019 period. The type of data used in this research is secondary data. The population that will be used in this study is all banks listed on the IDX in the 2015–2019 period. The results of this study indicate that there is a significant positive effect between investment decisions on firm value with a probability value of 0.0006; there is a significant positive effect between funding decisions on firm value with a probability value of 0.0193; there is a significant effect between dividend policy on firm value with a probability value of 0.0058; and there is a significant mediating effect by dividend policy on the relationship between investment decisions and firm value and on the relationship between funding decisions and firm value..